2018
DOI: 10.1111/asj.13062
|View full text |Cite
|
Sign up to set email alerts
|

Milk compositional changes of Laoshan goat milk from partum up to 261 days postpartum

Abstract: Despite the global increasing demand for goat milk, no data exist on the nutrient potential of Laoshan goat milk and limited information exists on its composition according to lactation period. In this study, the measured indicators, including dry matter, protein, immunoglobulin, lactoferrin, fat, ash, lactose, calcium, titratable acidity and pH from partum to 261 days postpartum of Laoshan goat milk, followed the same law of change. There was a significant difference over the first 5 days postpartum, after wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Protein in milk was determined using the method ISO 8969‐1 for nitrogen content estimation using the Kjeldahl Principle as followed by Chen et al., (2018). Lactose, the reducing sugar in milk was estimated using the Lane–Eynon method IS 1479 (Part II) as described in Hansen and Ferrão (2018) and Lane and Eynon (1934).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein in milk was determined using the method ISO 8969‐1 for nitrogen content estimation using the Kjeldahl Principle as followed by Chen et al., (2018). Lactose, the reducing sugar in milk was estimated using the Lane–Eynon method IS 1479 (Part II) as described in Hansen and Ferrão (2018) and Lane and Eynon (1934).…”
Section: Methodsmentioning
confidence: 99%
“…Calcium content in milk was estimated using ISO 12081 titrimetric method as followed by Chen et al. (2018) and Poitevin (2016). The calcium present in milk was precipitated as calcium oxalate and estimated by titrating it against potassium permanganate.…”
Section: Methodsmentioning
confidence: 99%
“…Both miRNAs can regulate the LTF gene, a member of the transferrin family with protein products existing in neutrophil secondary particles. The protein is the main iron binding protein in milk and human body secretions, and its antimicrobial activity makes it an important part of the nonspecific immune system [63,64]. Our results showed that the expression level of LTF at LG stage was significantly higher than that at the LL and DP stages, which is closely related to the higher levels of LTF in colostrum, thus directly and indirectly protecting the newborn from bacterial and other microbial infections.…”
Section: Discussionmentioning
confidence: 67%
“…In the latest study, the addition of quinoa extraction to goat milk yogurt enhanced the quality of the final products in terms of apparent viscosity, microstructure and organoleptic acceptability (El‐Shafei et al ., 2019). As a protein that plays an important role in functional dairy products, casein (CN) is one of the most abundant proteins in goat milk, accounting for approximately 70% of the total protein (Sun et al ., 2020), and the content of casein can change over time during the lactation period (Chen et al ., 2018; Mal et al ., 2018). CN is responsible for most of the unique physical properties of milk.…”
Section: Introductionmentioning
confidence: 99%